2007
DOI: 10.1021/bi701236f
|View full text |Cite
|
Sign up to set email alerts
|

An Alternate Mechanism of Abortive Release Marked by the Formation of Very Long Abortive Transcripts

Abstract: The Esigma70-dependent N25 promoter is rate-limited at promoter escape. Here, RNA polymerase repeatedly initiates and aborts transcription, giving rise to a ladder of short RNAs 2-11 nucleotides long. Certain mutations in the initial transcribed sequence (ITS) of N25 lengthen the abortive initiation program, resulting in the release of very long abortive transcripts (VLATs) 16-19 nucleotides long. This phenomenon is completely dependent on sequences within the first 20 bases of the ITS since altering sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…4). The transition from abortive to productive elongation, marked by release of σ 70 from promoter contacts (or from RNAP contacts), occurs within the first 20 nt of transcript elongation (Chander et al, 2007; Revyakin et al, 2006). Known cases of σ 70 -stimulated pausing in vivo occur no later than +25 (Ring et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…4). The transition from abortive to productive elongation, marked by release of σ 70 from promoter contacts (or from RNAP contacts), occurs within the first 20 nt of transcript elongation (Chander et al, 2007; Revyakin et al, 2006). Known cases of σ 70 -stimulated pausing in vivo occur no later than +25 (Ring et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…S1). We note the accumulation of abortive RNA products in reactions performed with template #2, which we attribute to the two base pair substitutions in the initial transcribed region; initial transcribed region alterations can have dramatic effects on abortive transcript production (Hsu et al 2003;Chander et al 2007). The ;116-nt terminated transcript (T) is indicated, and the asterisk (*) indicates a shorter terminated transcript that is the result of transcription initiating under the control of the promoter-distal extended À10 element.…”
mentioning
confidence: 86%
“…Kammerer et al (59) showed that the bacteriophage T5 N25 promoter and its derivative, the N25 antipromoter, exhibit very different rates of promoter escape (roughly 1.7 and 0.6 min –1 , respectively) and ratios of abortive to productive transcripts (40 and 300, respectively), despite differing only in the initial portion of their transcribed sequences (+3 to +20). Chander et al (60) demonstrated finer tuning using individual mutations to the 20-nucleotide sequence. These changes should in principle introduce a vertical scaling of the expression response curve.…”
Section: Biological Options For Tuningmentioning
confidence: 99%